Environmental & architectural phenomenology. Vol. 5, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 1994)
Vol. 5, No. 2, Spring 1994 (includes “items of interest,” "citations received,” book reviews of Jochen Bockemuhl's A Phenomenology of the Etheric World & Olof Alexandersson's Living Water, and essays by Cary de Wit & Louise Million).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals